Pembuatan Penyaring Air Untuk Peternak Ayam Petelur Di Dusun I Kubu Cubadak Simpang Petai - Anhar; Nurhalim Nurhalim; Feri Candra; Antonius Rajagukguk; Eddy Hamdani (LPPM UMRI, 2021)
In order to supply the water for laying hens farm in Kubu Cubadak Simpang Petai, the service team from University of Riau has designed a water purification system using the filtration technique. Before designing the filtration, sample of water from the well around the farm is taken and analyzed in the laboratory. Based on this result, the filtration is characterized to get the water satisfying the needs of the farm. There are two tubs in the filtration system containing silica sand, zeolite, and active carbon. Water from the well is pumped to the tank with three-meter height. From there, water is pumped back again to the tube to get the optimal water flow. The quality of water from the filtration have enhancement in terms of color, turbidity, and pH. The color and turbidity of water are improved from 41 NTU to 0 NTU and from 22,5 NTU to 5,59 NTU, respectively. Furthermore, there is an increasing in pH of water, from 5,44 to 6,32. These results have fulfilled the standard for laying hens farm.